St. Lucia : Request for Disbursement Under the Rapid Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses St. Lucia's Request for Disbursement Under the Rapid Credit Facility. IMF financing support provides resources to the countries' authorities for essential health-related expenditures and income support to ease the impact of coronavirus disease 2019 on the population. In order to address the pandemic, the authorities announced measures to help employees and households, including income support to the unemployed, tax relief, and providing cash transfers to the most vulnerable and affected. The countries' governments have responded to the pandemic by swiftly implementing containment measures, allocating scarce budgetary resources to critical health care spending, and introducing income support to the most affected sectors and households. Protection of the financial system will help cushion the economic impact of the pandemic. Measures have also been taken by the Eastern Caribbean Central Bank to facilitate the provision of credit and safeguard financial stability. The IMF will continue to be engaged with Dominica, Grenada, and St. Lucia, and stands ready to provide policy advice and further support as needed.